2018
DOI: 10.21037/jovs.2018.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Application of the coaxial smart drain in patients with a large air leak following anatomic lung resection: a prospective multicenter phase II analysis of efficacy and safety

Abstract: Our experience with this novel Coaxial Drain was satisfactory with no clinically relevant complication caused using this drain, no need to insert additional drain or replace the existing one with another drain a duration of air leak and chest tubes as well as the incidence of subcutaneous emphysema that was in line with what observed in the daily practice in similar highly selected patients with large air leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Compared with STs, the draining surface area provided by SDC is considerably wider and resistant to clot occlusion. Furthermore, Guerrera et al showed that SDC provides a satisfactory air evacuation even in patients with significant air leaks [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with STs, the draining surface area provided by SDC is considerably wider and resistant to clot occlusion. Furthermore, Guerrera et al showed that SDC provides a satisfactory air evacuation even in patients with significant air leaks [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with STs, the draining surface area provided by SDC is considerably wider and resistant to clot occlusion. Furthermore, Guerrera et al showed that SDC provides a satisfactory air evacuation even in patients with signi cant air leaks (14).…”
Section: Discussionmentioning
confidence: 99%
“…The trial was designed to test the hypothesis that the amount of pleural fluid after uniportal VATS upper lobectomy with a smart coaxial drain is superior (based on a previous study in triportal VATS and open surgery [17,18]) to uniportal VATS with a standard drain.…”
Section: Sample Sizementioning
confidence: 99%